Impact of rotating machines on harmonic distortion in power distribution systems - Muhamad Iszuan, Hamdan (2009)
Harmonic cause of distortion of the voltages and current waveforms, which have adverse effects on electrical equipment. Harmonics are one of the major power quality concerns. The estimation of harmonics from nonlinear loads is the first step in a harmonic analysis and this may not be straight forward. Rotating machines are considered sources of harmonics because the windings are embedded in slots which are not perfectly sinusoidally distributed resulting in a distorted mmf. Nonsinusoidal voltage applied to electric machines may cause overheating, pulsating torques or noise. In additional to cross the line applications, adjustable speed drive motors are fed from inverter that can produce significant voltage distortion. In induction motor, they can overheat due to the effects of harmonic currents, depending on their frequency, because of additional rotating magnetic fields in the motor. Harmonic produce harmonic fluxes in motors. The harmonic torques tends to rotate motor at different harmonic synchronous speeds. It can produce high frequency currents in rotor circuits. The data which collect from the site project will be inserting into Visualation Basic, VB. The parameters that will be state are voltage, current, frequency, time and total harmonic distortion. The reading will be collect with the different speed of motor. It causes to show how the speeds of motor produce harmonic distortion. Then it wills using the different type of starter motor there are Direct-On-Line, Auto-Transformer and Star-Delta.